Smart Cities for People with IDD - Foundations for Digitally Inclusive Healthcare Ecosystems - Badr Nabil Georges (ITM Web of Conferences, 2023)
Smart cities require smart healthcare. In a smart city, the purpose of citywide efforts has the fundamental objectives of livability, sustainability, and productivity. Some well-intentioned smart city programs unintentionally worsen inequality when they lack transparency, fail to involve the community or ignore the varied requirements and preferences of residents. To address ongoing health disparities among persons with intellectual disabilities, patient-centred preventive healthcare that considers both their physical and mental health needs must be prioritized. Engagement and inclusion must at the forefront of smart city initiatives that shift from being technology-centric to citizen-centric. We bring attention to pillars of interaction in inclusive smart cities in the context of care for people with intellectual and developmental disabilities. We explore the fundamentals of a digitally inclusive healthcare service ecosystem for people with IDD through the lens of the Actor for Actor framework to learn about the foundational facilities for IDD patients’ to engage an establish care pathways.